Intermittent pneumatic compression versus additional prophylaxis with enoxaparin for prevention of venous thromboembolism after laparoscopic surgery for gastric and colorectal malignancies: multicentre randomized clinical trial. Issue 5 (23rd July 2020) - Kamachi, H.; Homma, S.; Kawamura, H.; Yoshida, T.; Ohno, Y.; Ichikawa, N.; Yokota, R.; Funakoshi, T.; Maeda, Y.; Takahashi, N.; Amano, T.; Taketomi, A.
Abstract : Background: The role of antithrombotic chemoprophylaxis in prevention of venous thromboembolism (VTE) in laparoscopic surgery for gastric and colorectal malignancies is unknown. This study compared the addition of enoxaparin following intermittent pneumatic compression (IPC) with IPC alone in patients undergoing laparoscopic surgery for gastrointestinal malignancy. Methods: In this multicentre RCT, eligible patients were older than 40 years and had a WHO performance status of 0 or 1. Exclusion criteria were prescription of antiplatelet or anticoagulant drugs and history of VTE. Patients were allocated to IPC or to ICP with enoxaparin in a 1 : 1 ratio. Stratification factors included sex, location of cancer, age 61 years and over, and institution. Enoxaparin was administered on days 1–7 after surgery. Primary outcome was VTE, evaluated by multidetector CT on day 7. Results: Of 448 patients randomized, 208 in the IPC group and 182 in the IPC with enoxaparin group were evaluated. VTE occurred in ten patients (4·8 per cent) in the IPC group and six (3·3 per cent) in the IPC with enoxaparin group ( P  = 0·453). Proximal deep vein thrombosis and/or pulmonary embolism occurred in seven patients (3·4 per cent) in the IPC group and one patient (0·5 per cent) in the IPC with enoxaparin group ( P  = 0·050). All VTE events were asymptomatic and non‐fatal. Bleeding occurred in 11 of 202 patients in the IPC with enoxaparin group, and one patient needed a transfusion. All bleeding events were managed by discontinuation of the drug. Conclusion: IPC with enoxaparin after laparoscopic surgery for gastric and colorectal malignancies did not reduce the rate of VTE. Registration number: UMIN000011667 ( https://www.umin.ac.jp/ ). Abstract : This RCT compared intermittent pneumatic compression (IPC) alone with IPC plus enoxaparin for 1 week after surgery in the prevention of venous thromboembolism (VTE) in patients undergoing laparoscopic surgery for gastric or colorectal malignancy. Although VTE occurred in 4·8 per cent of the ICP‐alone group and 3·3 per cent of the ICP with enoxaparin group ( P  = 0·453), the occurrence of proximal deep vein thrombosis and/or pulmonary embolism was reduced from 3·4 to 0·5 per cent by the addition of enoxaparin ( P  = 0·050). No additional value of enoxaparin in patients who recover uneventful Abstract : Antecedentes: El papel de la quimioprofilaxis para la prevención del tromboembolismo venoso ( venous thromboembolism, VTE) en la cirugía laparoscópica de los tumores malignos gástricos y colorrectales se desconoce. El objetivo de este estudio fue comparar la quimioprofilaxis antitrombótica (enoxaparina) y la compresión neumática intermitente ( intermittent pneumatic compression, IPC) en pacientes sometidos a cirugía laparoscópica de tumores malignos abdominales. Métodos: Se efectuó un ensayo aleatorizado, controlado y multicéntrico de pacientes sometidos a cirugía laparoscópica de tumores gástricos y colorrectales en Japón. Los criterios de inclusión eran pacientes mayores de 40 años de edad y con un estado funcional de WHO de 0‐1. Los criterios de exclusión fueron la prescripción al paciente de fármacos antiagregantes o anticoagulantes y la historia de VTE. Los pacientes fueron asignados a IPC y ICP con la adición de enoxaparina en una relación 1:1. Los factores de estratificación incluyeron el sexo, la localización del cáncer, la edad mayor o menor de 61 años, y la institución. La enoxaparina fue administrada en los días postoperatorios ( postoperative day, POD) 1‐7. El resultado primario fue la VTE evaluada mediante tomografía computarizada multidetector en el POD7. Los cálculos de la potencia determinaron que se requerían 184 pacientes en cada grupo. Resultados: De los 448 pacientes aleatorizados, se evaluaron finalmente 208 pacientes en el grupo IPC y 182 pacientes en el grupo IPC más enoxaparina. La VTE ocurrió en 10 de 208 pacientes en el grupo IPC (4, 8%) y 6 de 182 pacientes en el grupo IPC más enoxaparina (3, 3%) ( P = 0, 45). La trombosis venosa profunda proximal ( proximal deep vein thrombosis, DVT) y/o el embolismo pulmonar ( pulmonary embolism, PE) ocurrieron en 7 de 208 pacientes en el grupo IPC (3, 4%) y 1 de 182 pacientes en el grupo IPC más enoxaparina (0, 55%) (riesgo relativo 0, 163, i.c. del 95% 0, 020‐1, 314, P = 0, 0503). Todos los eventos de VTE fueron asintomáticos y no mortales. Se produjo una hemorragia en 11 de 202 pacientes en el grupo IPC con enoxaparina (5, 4%, i.c. del 95% 3, 1%‐9, 5%, P < 0, 001), y un paciente precisó transfusión. Todos los eventos hemorrágicos pudieron ser tratados con la interrupción del fármaco. Conclusión: La IPC con la adición de enoxaparina tras cirugía laparoscópica de los tumores malignos gástricos y colorrectales no disminuye la VTE.